Persepsi Akuntan terhadap Akuntansi Sosial dan Lingkungan: Survei pada Akuntan Profesional - Putuhena, Hempry; Zalni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2026)
Social and environmental issues have become a key factor in investment decision-making and business strategies of modern companies. This study examines accountants' perceptions of social and environmental accounting (SEA), which is increasingly important for corporate transparency, accountability, and sustainability. This study uses a survey approach to 68 professional accountants using convenience sampling techniques. Surveys and empirical studies found that accountants generally view SEA positively and recognize its central role in reporting relevant to stakeholders. However, the implementation of SEA remains challenged, particularly in reporting standards, sustainability understanding, and institutional support. These findings underscore the need for strengthening accountants' competencies, harmonizing standards, and continuing education to support the effectiveness of SEA reporting in the future.